The Influence Of Quality Of Working Life On Employee Performance Mediated By Job Satisfaction Of Netira Embroidery UMKM Tasikmalaya City - Riyadi, Muhammad Aldi; Rahwana, Kusuma Agdhi; Asyiah, Ai Kusmiati (Journal of Management, Economic, and Accounting, 2024)
This research aims to determine the effect of quality of work life on employee performance which is mediated by job satisfaction of the netira embroidery SMEs in the city of Tasikmalaya. This type of research uses quantitative research methods. Data analysis used is linear regression and path analysis. The population in this study was 44 Netira Embroidery employees, the sampling technique used total sampling. Data was obtained using a questionnaire which was directly given to production employees, then the data was analyzed using lines. The results of data analysis showed that there was a significant influence between the variables of the quality of work life (X) on job satisfaction (Z). There is a significant effect between the quality of work life (X) on employee performance (Y) There is a significant effect between the variables Job Satisfaction (Z) on Employee Performance (Y) and Job Satisfaction (Z) mediates the relationship between the quality of work life (X) on Employee Performance (Y) at Netira Embroidery, Tasikmalaya City.